Genetic Vaccination against Coccidioides immitis: Comparison of Vaccine Efficacy of Recombinant Antigen 2 and Antigen 2 cDNA - Jiang, Chengyong (American Society for Microbiology, 1999)
Previous studies from our laboratory established that C-ASWS, an alkali-soluble, water-soluble extract from cell walls of Coccidioides immitis, protects mice against lethal challenge with this fungus. The C-ASWS extract contains a glycosylated protein, designated antigen 2 (Ag2), and a polysaccharide antigen. We recently cloned Ag2 cDNA and showed that the recombinant fusion protein elicited strong delayed-type hypersensitivity responses in immunized mice. This investigation was undertaken to determine if the recombinant Ag2 protein, expressed as an Ag2-glutathione S-transferase (GST) fusion protein, or Ag2 cDNA would protect mice against lethal challenge with C. immitis. The recombinant Ag2-GST protein protected BALB/c mice against intraperitoneal challenge with 250 arthroconidia, as assessed by a decrease in fungal CFU in tissues. The Ag2-GST-immunized mice did not show, however, an increased survival during a 30-day period postinfection. By contrast, immunization of mice with Ag2 cDNA ligated into the pVR1012 plasmid engendered protection against intraperitoneal challenge with 2,500 arthroconidia and against pulmonary challenge with 50 arthroconidia. Vaccine efficacy paralleled the development of delayed-type hypersensitivity responses to C. immitis antigen. Whereas mice vaccinated with the recombinant Ag2-GST protein did not mount footpad hypersensitivity to C-ASWS or the recombinant Ag2-GST protein, mice vaccinated with the pVR1012-Ag2 construct mounted a strong footpad hypersensitivity and their spleen cells secreted gamma interferon upon in vitro stimulation with the Ag2-containing C-ASWS extract. This is the first investigation to show that genetic immunization can protect against lethal challenge with C. immitis.